2013
DOI: 10.3390/app3030593
|View full text |Cite
|
Sign up to set email alerts
|

Routine Production of 89Zr Using an Automated Module

Abstract: 89Zr has emerged as a useful radioisotope for targeted molecular imaging via positron emission tomography (PET) in both animal models and humans. This isotope is particularly attractive for cancer research because its half-life (t 1/2 = 3.27 days) is well-suited for in vivo targeting of macromolecules and nanoparticles to cell surface antigens expressed by cancer cells. Furthermore, 89Zr emits a low-energy positron (E β+,mean = 0.40 MeV), which is favorable for high spatial resolution in PET, with an adequate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 52 publications
4
28
0
2
Order By: Relevance
“…This is in agreement with our EoB DFO ESA results for 89 Zr produced through previous methods of 60 ± 50 GBq/μmol (n = 124). Additionally, these results are in agreement with EOB DFO ESA values of 17 – 44 GBq/μmole reported by Holland et al (2009) and those of 4 ± 4 GBq/μmole reported by Wooten et al (2013). It is possible that the higher run-to-run variability in ESA values measured in the current work is as a result of the spot welding method potentially resulting in higher trace metal contamination of the 89 Zr through the presence of the cooling-water-contacted Ta backing, high-proton-current sputtered degrader foil material, or from the welding electrode.…”
Section: Resultssupporting
confidence: 92%
“…This is in agreement with our EoB DFO ESA results for 89 Zr produced through previous methods of 60 ± 50 GBq/μmol (n = 124). Additionally, these results are in agreement with EOB DFO ESA values of 17 – 44 GBq/μmole reported by Holland et al (2009) and those of 4 ± 4 GBq/μmole reported by Wooten et al (2013). It is possible that the higher run-to-run variability in ESA values measured in the current work is as a result of the spot welding method potentially resulting in higher trace metal contamination of the 89 Zr through the presence of the cooling-water-contacted Ta backing, high-proton-current sputtered degrader foil material, or from the welding electrode.…”
Section: Resultssupporting
confidence: 92%
“…Briefly, 89 Zr-oxalate was produced via the Y-89(p,n)Zr-89 reaction on the CS-15 cyclotron (Cyclotron Corporation, Berkeley, CA) and purified with an in-house automated module[2728]. The resulting [ 89 Zr]oxalate was produced with a specific-activity of 8.1–15.4 GBq/μmol (220–418 mCi/μmol).…”
Section: Methodsmentioning
confidence: 99%
“…The use of 89 Zr is constantly evolving and it is expected that in the near future this radionuclide will be widely applied in a PET imaging. The emission of b + (E mean = 0.66 MeV and E max = 1.5 MeV) from 90 Nb makes it especially promising for the immuno-PET and clinical applications [11,12]. Only limited excitation functions for the alpha-induced reactions on 89 Y are available in the various energy ranges [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%